2023
DOI: 10.3390/cancers15051563
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil Suppresses Colon Tumor through Activating the p53-Fas Pathway to Sensitize Myeloid-Derived Suppressor Cells to FasL+ Cytotoxic T Lymphocyte Cytotoxicity

Abstract: Myelosuppression is a major adverse effect of 5-fluorouracil (5-FU) chemotherapy. However, recent findings indicate that 5-FU selectively suppresses myeloid-derived suppressor cells (MDSCs), to enhance antitumor immunity in tumor-bearing mice. 5-FU-mediated myelosuppression may thus have a beneficial effect for cancer patients. The molecular mechanism underlying 5-FU’s suppression of MDSCs is currently unknown. We aimed at testing the hypothesis that 5-FU suppresses MDSCs through enhancing MDSC sensitivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…5-FU is a well-known drug that induces apoptosis in CRC cells as a response to upregulation and accumulation of p53 [ 29 ]. As expected, the cytotoxic effects of 5-FU on HCT116 p53 −/− cells were less pronounced than those against HCT116 wild-type (WT) cells ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…5-FU is a well-known drug that induces apoptosis in CRC cells as a response to upregulation and accumulation of p53 [ 29 ]. As expected, the cytotoxic effects of 5-FU on HCT116 p53 −/− cells were less pronounced than those against HCT116 wild-type (WT) cells ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“… 42 (4) Direct elimination. Some therapeutic drugs containing gemcitabine, 43 docetaxel, 44 and 5-fluorouracil 45 have been reported to remove MDSCs. Our data showed that SFN repressed MDSCs immunosuppression by directly inducing apoptosis and constitutes a basis for testing SFN as a strategy to eliminate MDSCs in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Antineoplastic agents have been found to increase the frequency and number of MDSCs in the circulating blood and tumor tissues of rodents and humans (44)(45)(46).Low-dose antineoplastic agents such as CPA and 5-Fu increase immunosuppressive proangiogenic Gr-1 + CD11b + BMDC levels, suggesting that they could promote tumor growth through the dual mechanism of enhancing angiogenesis and inhibiting immune function. The expressions of proangiogenic and immunomodulatory proteins in tumor tissues play an important role in tumor angiogenesis regulation, TME immune status, and the interplay between tumor-associated myeloid-cell-mediated immune suppression and angiogenesis (40,47,48).…”
Section: Discussionmentioning
confidence: 99%